Comparison of Furans Formation and Volatile Aldehydes Profiles of Four Different Vegetable Oils During Thermal Oxidation. Issue 7 (17th June 2019) - Wang, Yangling; Zhu, Mengting; Mei, Jiang; Luo, Shuhan; Leng, Tuo; Chen, Yi; Nie, Shaoping; Xie, Mingyong
Abstract : Abstract: The evolution of volatile aldehydes and the conversion of oxygenated ityβ‐unsaturated aldehydes (OαβUAs) into furans were compared in four vegetable oils (soybean oil, olive oil [OVO], peanut oil [PO], and perilla oil [PAO]) thermally oxidized at temperatures of 150, 180, and 210 °C for 10 hr/day over a 3‐day period. Results showed that 2 alkyl furans and 23 volatile aldehydes including 4 toxic OdβUAs were detected by GC‐MS. The original fatty acid compositions of the oils played a key role in the type and concentration of those volatile compounds. 4‐Hydroxy‐2‐hexenal (HHE) and ethyl furan were only detected in PAO with a high content of linolenic acid, while the greatest level of pentyl furan was detected in PO with abundant linoleic acid. Greater amounts of 4‐hydroxy‐(E)‐2‐nonenal (HNE) and 4‐oxo‐(E)‐2‐nonenal (ONE) were formed in the OVO with abundant oleic acid. The close relativity of HHE and ethyl furan was also demonstrated. With principal component analysis, these vegetable oils could be discriminated based on their fatty acids and volatile compounds. The loading plot confirmed that HHE and ethyl furan were derived from the linolenic acid oxidation and degradation. Practical Application: The chemometric results showed that the formation of the volatile components during heating in different vegetable oils has close correlation with the original fatty acids composition of vegetable oils. Our research has also confirmed the presence of toxic O ɑβ UAs in oils after heating. Considering that they are proven to generate lots of degenerative diseases, further studies are needed to establish the risk level of using certain oils in frying and seek effective methods to inhibit their formation.